Dampak Positif Eco-Print Sebagai Salah Satu Wujud Kreatifitas Warga Marinda - Achmad Djuraidi; Bambang Hadi Santoso; Nanis Setyorini; Hindah Mustika (Universitas Islam Nahdlatul Ulama Jepara, 2022)
One of the things that has become an icon for Marida residents is the existence of an ecoprint, apart from being a routine activity carried out by local residents, especially women, ecoprint can also be a place for the community to share knowledge and besides that it can also generate financial results. Ecoprint is one of the results that has many benefits so it needs to be preserved because it has a positive impact on local residents and residents around them. Elderly women in Marinda village can be said to be productive elderly because they can produce works that are not only creative but also innovative, of course this is a positive point that is always supported. Keywords: ecoprint, motivation,creation